WASH for WORMS: A Cluster-Randomized Controlled Trial of the Impact of a Community Integrated Water, Sanitation, and Hygiene and Deworming Intervention on Soil-Transmitted Helminth Infections - Vaz Nery, Susana (Am J Trop Med Hyg, 2019)
Water, sanitation, and hygiene (WASH) interventions have been proposed as an important complement to deworming programs for sustainable control of soil-transmitted helminth (STH) infections. We aimed to determine whether a community-based WASH program had additional benefits in reducing STH infections compared with community deworming alone. We conducted the WASH for WORMS cluster-randomized controlled trial in 18 rural communities in Timor-Leste. Intervention communities received a WASH intervention that provided access to an improved water source, promoted improved household sanitation, and encouraged handwashing with soap. All eligible community members in intervention and control arms received albendazole every 6 months for 2 years. The primary outcomes were infection with each STH, measured using multiplex real-time quantitative polymerase chain reaction. We compared outcomes between study arms using generalized linear mixed models, accounting for clustering at community, household, and individual levels. At study completion, the integrated WASH and deworming intervention did not have an effect on infection with Ascaris spp. (relative risk [RR] 2.87, 95% confidence interval [CI]: 0.66–12.48, P = 0.159) or Necator americanus (RR 0.99, 95% CI: 0.52–1.89, P = 0.987), compared with deworming alone. At the last follow-up, open defecation was practiced by 66.1% (95% CI: 54.2–80.2) of respondents in the control arm versus 40.2% (95% CI: 25.3–52.6) of respondents in the intervention arm (P = 0.005). We found no evidence that the WASH intervention resulted in additional reductions in STH infections beyond that achieved with deworming alone over the 2-year trial period. The role of WASH on STH infections over a longer period of time and in the absence of deworming remains to be determined.